Identity, Lifestyle, and Halal Consumption: A Study on Muslimah Socialites in Pontianak City - Sari, Intan Purnama; Atmaja, Dwi Surya; Luqman, Luqman (Majapahit Journal of Islamic Finance and Management, 2025)
This study explores how Muslimah socialites in Pontianak City construct their identity and lifestyle through halal consumption practices. Utilizing a qualitative descriptive method with symbolic consumption theory and the Theory of Planned Behavior (TPB), this research investigates how personal religiosity, community influence, and aesthetic preferences shape consumer behavior in fashion and cosmetics. Data were collected through in-depth interviews with five informants, participatory observation, and documentation. The findings show that halal consumption is not merely a religious obligation but functions as a form of identity performance and symbolic status assertion. Muslimah socialites integrate modest fashion and halal beauty products to project an image of being pious yet modern, supported by their social environment and digital platforms. This study contributes to understanding the performative nature of halal consumption in urban Muslim women's everyday lives and offers insights for policymakers and halal product developers targeting the Muslim lifestyle segment.